Employment duration of Polish Ekstraklasa Managers, and its impact on or-ganizations sport success - Marcin Karwiński (Nicolaus Copernicus University in Toruń, 2016)
Sports team as a integral part of the organization, plays an important part in building its success and its effectiveness impacts the perception of the whole organization. Proper team management plays a key role in building sports success, which leads to a conclusion that a position of a manager in football is a position of a high importance. The duration of the employment on that position varies and often is shorter than a year. That raises a question about the impact of manager's employment stability on sports team's performance. The author compared the duration of manager's employment in polish Ekstraklasa teams over last eleven seasons with the performance of the teams, that comparison led to a conclusion that there is no evident connection between the two, but it can be observed that higher stability often leads to better results. The research is going to be widened and continued to achieve deeper insight on the problem.